Productivity, Competence and Middle Income Trap: The Malaysian Scenario - Kunjiapu, Shamuni; Hanip, ohamad Fariz Mohamad (The journal of contemporary issues in business and government, 2021)
This paper provides an overview of the Malaysian productivity and competence related issues in Malaysia. Being an emerging economy, low productivity and low competence easily sends Malaysia spiralling down into the Middle-Income Trap (MIT). The first part of this paper discusses issues related to labour productivity, labour competence, and Middle-Income Trap. The second part looks at possible strategies aimed at overcoming these.